Long-term results of ablation index guided atrial fibrillation ablation: insights after 5+ years of follow-up from the MPH AF Ablation Registry - Fitzpatrick, N.; Herczeg, S.; Hong, K.; Seaver, F.; Rosalejos, L.; Boles, U.; Jauvert, G.; Keelan, E.; O’Brien, J.; Tahin, T.; Galvin, J.; Széplaki, G. (Frontiers in Cardiovascular Medicine, 2024)
Background Catheter ablation (CA) for symptomatic atrial fibrillation (AF) offers the best outcomes for patients. Despite the benefits of CA, a significant proportion of patients suffer a recurrence; hence, there is scope to potentially improve outcomes through technical innovations such as ablation index (AI) guidance during AF ablation. We present real-world 5-year follow-up data of AI-guided pulmonary vein isolation. Methods We retrospectively followed 123 consecutive patients who underwent AI-guided CA shortly after its introduction to routine practice. Data were collected from the MPH AF Ablation Registry with the approval of the institutional research board. Results Our patient cohort was older, with higher BMI, greater CHA2DS2-VASc scores, and larger left atrial sizes compared to similar previously published cohorts, while gender balance and other characteristics were similar. The probability of freedom from atrial arrhythmia with repeat procedures is as follows: year 1: 0.95, year 2: 0.92, year 3: 0.85, year 4: 0.79, and year 5: 0.72. Age >75 years (p = 0.02, HR: 2.7, CI: 1.14–6.7), BMI >35 kg/m2 (p = 0.0009, HR: 4.6, CI: 1.8–11.4), and left atrial width as measured on CT in the upper quartile (p = 0.04, HR: 2.5, CI: 1–5.7) were statistically significant independent predictors of recurrent AF. Conclusion AI-guided CA is an effective treatment for AF, with 95.8% of patients remaining free from atrial arrhythmia at 1 year and 72.3% at 5 years, allowing for repeat procedures. It is safe with a low major complication rate of 1.25%. Age >75 years, BMI >35 kg/m2, and markedly enlarged atria were associated with higher recurrence rates.